Polyvinylchloride-packaged loin strip steaks from vacuum-packaged beef strip loins decontaminated with lactic acid and stored for up to 126 days - Mease, L.E.; Kropf, Donald H.; Prasai, R.K.; Kenney, P.B.; Vogt, L.R.; Fung, Daniel Y. C.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Aerobic plate counts (APCs), presence/ absence of Listeria monocytogenes and Salmonella spp., and visual color evaluations were used to determine the microbiological and display quality of steaks fabricated from beef strip loins sprayed with lactic acid (1.5% v/v) or water before, after, o r both before and after vacuum storage (14, 28, 56, 84, or 126 days) at either 30E or 36EF compared to nonsprayed or nonstored controls. Lactic acid applied pre- and poststorage (126 days) at 30EF reduced APCs of steak s up to 2 log (99%). L. monocytogenes and Salmonella spp. were absent from all steaks. Lactic acid caused slightly more rapid color deterioration, resulting in slightly shorter display-life for steaks.
Keywords: Beef; Decontamination; Lactic acid; Beef steaks; Display; Color; Bacteria